The Expulsion of Hagar - Englard, Yaffa (Religion and the arts, 2018)
Although many other scenes from the book of Genesis have been represented visually over the centuries, Hagar’s expulsion has been largely overlooked. This article examines the history of those works devoted to the subject, focusing in particular on the planes on which Abraham, Sarah, and Hagar are placed, the effects of narrative and story-telling upon visual art, the influence of theological stances and their developments upon the understanding of the episode, its reflection of early and medieval Jewish-Christian relations, and feminist/gender biblical interpretation.